Educators' Life Skills in the Era of Smart Society 5.0 - Saputra, Aan Endaniyar; Mirsafa, Ludya (JUPE : Jurnal Pendidikan Mandala, 2023)
AbstractEducators as one of the components of national education that have an important role in an educational institution. Seknun stated that "the educator as a teacher is someone who must be treated and imitated. Digugu means that everything that is conveyed is always believed and believed to be the truth by all his disciples. All knowledge that comes from the teacher is made as a truth that does not need to be proven or examined again. Imitated means to be a role model and role model for his students, starting from the way and way of thinking, how to speak to the way of behaving everyday. Thus, teachers have a very large role in the implementation of learning or education." (Seknun, 2012). Teachers are the figures who get along and interact with students the most compared to other personnel in the school. Teachers are tasked with planning and implementing the learning process, assessing learning outcomes, conducting guidance and training, conducting research and studies, and opening communication with the community.